2010
DOI: 10.1111/j.1462-5822.2010.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-derived neutrophil-activating protein increases the lifespan of monocytes and neutrophils

Abstract: SummaryAn invariable feature of Helicobacter pyloriinfected gastric mucosa is the persistent infiltration of inflammatory cells. The neutrophilactivating protein (HP-NAP) has a pivotal role in triggering and orchestrating the phlogistic process associated with H. pylori infection. Aim of this study was to address whether HP-NAP might further contribute to the inflammation by increasing the lifespan of inflammatory cells. We report that HP-NAP is able to prolong the lifespan of monocytes, in parallel with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…For such a purpose, slan + monocytes and, for comparison, autologous CD14 + monocytes, were cultured for up to 8 d in vitro, either in control medium or in supernatants derived from primary colon adenocarcinoma (SW480) and matched lymph node metastatic (SW620) cell lines or from a breast carcinoma cell line (MCF7). By doing so, first of all we noticed that, consistent with previous data, the viability of both slan + and CD14 + monocytes dramatically decreased within 1 d of incubation in control medium, reaching minimal values at, respectively, d 4 and 8 (Fig. A and D).…”
Section: Resultssupporting
confidence: 89%
“…For such a purpose, slan + monocytes and, for comparison, autologous CD14 + monocytes, were cultured for up to 8 d in vitro, either in control medium or in supernatants derived from primary colon adenocarcinoma (SW480) and matched lymph node metastatic (SW620) cell lines or from a breast carcinoma cell line (MCF7). By doing so, first of all we noticed that, consistent with previous data, the viability of both slan + and CD14 + monocytes dramatically decreased within 1 d of incubation in control medium, reaching minimal values at, respectively, d 4 and 8 (Fig. A and D).…”
Section: Resultssupporting
confidence: 89%
“…While NapA mediates damage to DNA by stimulating neutrophil to produce reactive oxide species, it protects DNA by combating oxidative stress with its ferroxidase center 15 , 16 . NapA neither has toxic effect on monocytes and neutrophils nor reduces their viability or lifespan, although it can enhance production of nitric oxide 17 , 18 . These data warrant approaches on application of NapA as a vaccine candidate or immunotherapy agent 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation in response to H. pylori infection may not only be induced by recruitment of leukocytes, but, alternatively, the induction of IL‐1β by H. pylori neutrophil‐activating protein (HP‐NAP) may increase survival of inflammatory monocytes, and in turn neutrophils extending the local life time of these cells, as shown by Cappon et al. [23]. Several studies have shed more light to the many facets of IL‐1β in this infection, such as the loosening of tight junctions by disrupting claudin‐4 [24], and the involvement of sonic hedge hog signaling in IL‐1‐dependent reduction in gastric acid output [25].…”
Section: Inflammatory and Innate Immune Response To Infectionmentioning
confidence: 99%
“…Wong et al [22] recent characterization of macrophage migration inhibitory factor (MIF) expression in mice infected with H. pylori revealed that a negligible inflammatory response in H. pylori-infected MIF-deficient mice correlated with a substantially reduced inflammatory T-cell response, characterized by lower IFN-c and TNF-a production. Inflammation in response to H. pylori infection may not only be induced by recruitment of leukocytes, but, alternatively, the induction of IL-1b by H. pylori neutrophil-activating protein (HP-NAP) may increase survival of inflammatory monocytes, and in turn neutrophils extending the local life time of these cells, as shown by Cappon et al [23]. Several studies have shed more light to the many facets of IL-1b in this infection, such as the loosening of tight junctions by disrupting claudin-4 [24], and the involvement of sonic hedge hog signaling in IL-1dependent reduction in gastric acid output [25].…”
Section: Innate Inflammatory Mediatorsmentioning
confidence: 99%